Diplonemids - Lukeš, Julius; Flegontova, Olga; Horák, Aleš (Current biology, 2015)
Lukeš et al. introduce an enigmatic group of unicellular eukaryotes called the diplonemids, which according to recent surveys may be widespread in marine ecosystems.
Keywords: Biodiversity; biodiverzita; Euglenozoa; Aquatic Organisms; vodní organismy